Nursing self care in sleep discorders - Dois, Angelina; Masalán, Patricia; Leyton, Paola (Investigación y Educación en Enfermería, 2008)
The ocjective of this research is to know the perception of effectiveness of the Self Care Nursing Program un adults with sleep disorders treated in the Medical Sleep Center of the Catholic University of Chile (CEMS) between 1999 and 2000, in in Santiago de Chile. It is a descriptive, exploratory, retrospective study, with a sample of 25 adults, constituted in a 72% by women, 52% of people has between 20 and 39 years, 78% classify in a high and medium-high socio-economic level, the 100% have complete high school education, and the most frequently sleep problem is the conciliation insomnia. More of 80% consumes sleeping pills, 85% of them refers to have disminished the doses during and after attending the Self-Care Nursing Program. 84% of the interviewed people at the moment uses some of the learned techniques: 36% sleep hygiene, 12% relaxation and imaginary and 36% both. 80% perceived as benefits of the nursing program the improvement in the quality of the sleep and a sensation of serenity and tranquillity in their daily live, by that is better quality of life. Key Words: Sleep, Mental Healt.